Engaging Senior High Students in Automated Written Corrective Feedback on Writing Skills - Pradana, Galih Rayi (Peneliti.net, 2024)
Writing skills are the skills that are also important in English learning activities. Students feel afraid when conveying anything about writing skills in English learning activities especially grammar. This study intends to engage students in analyzing grammatical errors in a text. The texts that the author evaluated with the students were recount text and texts that they had independently composed so that they could repair the errors in their writing. In this instance, the author advised them to utilize Grammarly application to improve their writing abilities. This study employs qualitative descriptive research to determine how effectively participants can use grammatical applications to correct vocabulary problems. The author also provided incentives and additional direction during the research process so that students are more passionate about adopting the use of grammar, whether they are examining narrative materials or their texts for grammatical problems. Grammarly can be viewed as a tool for enhancing vocabulary or grammar knowledge and motivating correcting grammatical errors in the text. Their new understanding of writing skills improved.